Regulatory Pathway for Licensing Biotherapeutics in Mexico - López-Morales, Carlos A.; Tenorio-Calvo, Alejandra; Cruz-Rodríguez, Rodolfo; Sánchez y Tepoz, Julio; Belgharbi, Lahouari; Pérez-Tapia, Sonia Mayra; Medina-Rivero, Emilio (Frontiers in Medicine, 2018)
Biotherapeutic products which are derived from living organisms using recombinant DNA technology significantly contribute to the progress in the treatment of life-threatening and chronic diseases. The worldwide sale of biological drugs in 2016 was near US $263,700 million. In Latin America, where monoclonal antibodies market was worth US $7000 million, being Mexico the second largest market. Approval is one of the key aspects which influences the market of medicinal products, thus it is responsibility of the regulatory authority to establish a regulatory framework that ensure safety and efficacy of the products, and it is responsibility of the applicants to provide a high quality dossier in accordance with the registration requirements of the country. The applicants submitting registration requests in Mexico need to be aware of the requirements. Similar to many other countries, Mexico has adopted the Common Technical Document (CTD) structure for organizing dossier of the medicinal product for submission into main modules (i.e., quality, non-clinical, and clinical). This facilitates the submission process of medicinal products following a logical sequence aligned to the International Council on Harmonisation (ICH) guidelines. Moreover, this structure improves the transparency and clarity of the dossier in process of evaluation of medicinal products. In Mexico, the Ministry of Health has published a regulation, NOM-257-SSA1-2014, which established the general requirements to be followed by applicants to complete the registration of biotherapeutics. This regulation stipulates that the evaluation process is supported by a regulatory framework involving Good Manufacturing Practices, labeling, stability, clinical trials, biocomparability studies, pharmacovigilance, and a technical evaluation performed by a multidisciplinary team of experts in biotherapeutics development. Additionally, the Mexican regulatory agency, COFEPRIS, has published specific guidelines to facilitate the application process. Despite the availability of this information, the scope is limited to regulatory and administrative purposes, rather than technical-scientific supporting knowledge. The aim of this article is to provide concise information to improve and promote communication between industry and regulatory agencies. Herein, we describe the current process of COFEPRIS in regulating biotherapeutics in Mexico. This process explains the basis for the organization and structure of the technical-scientific information of biotherapeutics required for registration application